Transformation of Rural Patterns in Greece in a European Regional Development Perspective (The Case of Crete) - Andreas Tsatsaris; Polixeni Iliopoulou; Panagiotis Stratakis (European Regional Science Association (ERSA), 2006)
Rural space in Greece is experiencing a significant transformation. During the last four decades the traditional urban-rural dichotomy has given its place to complex spatial patterns which are in a process of continuous change. This change is the result of a variety of factors such as the international economic environment, the emergence of new economic activities in rural areas, mainly the service sector and tourism, the changing urban-rural relations as well as the implementation of national and European policies for the agricultural sector and for rural development. In addition, rural development is not any longer dependent solely on the agricultural sector but also on the rural- urban relationships and the presence of a large variety of economic activities in rural areas. In this paper data concerning demographic, economic and infrastructure characteristics of rural areas are analyzed for the last five population Censuses, describing the transformation of rural space in Greece. A number of typologies of rural areas in Greece are presented for different time periods which demonstrate the significant changes of rural patterns in the last two decades. These typologies are employed in order to suggest policy guidelines for rural development in Greece. The results will be presented in a GIS environment and when appropriate will be compared to similar studies in Europe. Finally policies for agricultural and rural development, in the context of European regional and spatial development, will be examined in relation to rural patterns in Greece and the development perspectives of rural areas.
Keywords: 330